Metabolic profile of extracts obtained from in vitro culture and field plants Morinda royoc L., Psidium guajava L. and Morus alba L. - Alina Capote (Biotecnología Vegetal, 2008)
The in vitro plant cell and tissue culture is an alternatives to identify new compounds or to increase production of well-known compounds useful for humankind. The aim of this work was to produce biomass of Morinda royoc L, Psidium guajava L var ‘EEA18-40’ and Morus alba L var ‘Criolla’ species. Different regeneration systems were used. Besides, profile of metabolites production in the in vitro cultured biomass and plants from field was determined by means of the combined techniques of liquid chromatography and mass spectrophotometer. In Shoots culture by in vitro culture system was more feasible for the production of biomass with bigger content of dry matter in Morinda royoc, compared with cells and callus system. Yields of extracts were always bigger in the in vitro culture systems than those obtained from field plants. Profiles of compounds detected in plants coming from greenhouses and in vitro cultured shoots were similar in Morinda royoc. Although, in Psidium guajava and Morus alba were different. Results demonstrated that in vitro culture is a potential source to identify and to produce new compounds. Key words: biomass, guava, in vitro regeneration systems, metabolites profile, morus